Modern Manuscripts and the Pre-History of Digital Humanities: Paper Processors. Alex Christie. - Du, Xingjie (Digital Scholarship in the Humanities, 2025)
The article focuses on Alex Christie's book, *Modern Manuscripts and the Pre-History of Digital Humanities: Paper Processors*, which explores the convergence of modern literary writing and digital media. Christie argues that the text processing methods used by modernist authors like Raymond Roussel, Marcel Proust, Samuel Beckett, and Mina Loy reveal a historical connection to contemporary digital practices. Through detailed analysis, the book illustrates how these authors employed innovative writing techniques that anticipate modern computational methods, suggesting that literary modernism and digital humanities can inform and enrich each other. Ultimately, Christie encourages readers to reconsider the relationship between literature and technology, highlighting the ongoing relevance of this dialogue in the context of rapid advancements in AI and digital media.